Passive, continuous monitoring of carbon dioxide geostorage using muon tomography. (10th December 2018) - Gluyas, Jon; Thompson, Lee; Allen, Dave; Benton, Charlotte; Chadwick, Paula; Clark, Sam; Klinger, Joel; Kudryavtsev, Vitaly; Lincoln, Darren; Maunder, Ben; Mitchell, Cathryn; Nolan, Sam; et al.
Abstract : Carbon capture and storage is a transition technology from a past and present fuelled by coal, oil and gas and a planned future dominated by renewable energy sources. The technology involves the capture of carbon dioxide emissions from fossil fuel power stations and other point sources, compression of the CO2 into a fluid, transporting it and injecting it deep beneath the Earth's surface into depleted petroleum reservoirs and other porous formations. Once injected, the CO2 must be monitored to ensure that it is emplaced and assimilated as planned and that none leaks back to surface. A variety of methods have been deployed to monitor the CO2 storage site and many such methods have been adapted from oilfield practice. However, such methods are commonly indirect, episodic, require active signal generation and remain expensive throughout the monitoring period that may last for hundreds of years. A modelling framework was developed to concurrently simulate CO2 geostorage conditions and background cosmic-ray muon tomography, in which the potential was assessed for using variations in muon attenuation, due to changes in CO2 abundance, as a means of CO2 detection. From this, we developed a passive, continuous monitoring method for CO2 storage sites using muon tomography, the tools for which can be deployed during the active drilling phase (development) of the storage site. To do this, it was necessary to develop a muon detector that could be used in the hostile environment (saline, high temperature) of the well bore. A prototype detector has been built and tested at the 1.1 km deep Boulby potash mine on the northeast coast of England, supported by the existing STFC Boulby Underground Laboratory on the site. The detector is now ready to be commercialized. This article is part of the Theo Murphy meeting issue 'Cosmic-ray muography'.